Long-Distance Transport of Prosystemin Messenger RNA in Tomato - Haiyan Zhang; Yuanyuan Hu; Yuanyuan Hu (Frontiers in Plant Science, 2017)
Main conclusion: The transcripts of transgenic prosystemin (PS) gene are mobile and the PS mRNA can be translated into protein in tomato and tobacco plants. Systemin (SYS) and its precursor protein, prosystemin (PS), are upstream components of the wound-induced signaling pathway in tomato. Although the mobile signal(s) for wound responses has been the subject of considerable research, its identity remains controversial. Intensive studies have revealed the essential role of mRNA on plant systemic signaling. We hypothesize that PS mRNA can act as a transmissible signal in tomato. Herein, we demonstrated that transgenic PS mRNA occurs in leaves located at considerable distances from the initial site of its generation by a transient Agrobacterium-infiltration assay system. We also showed that PS protein is present in the vascular bundle of the distant leaves. Our results indicate that transgenic PS mRNA may be functional as a long-distance signal to modulate systemic defense responses in tomato, providing novel insights into the multifaceted systems by which SYS signaling transports.